Upaya Pencegahan Stunting Melalui Pemberian Makanan Tambahan Pada Balita Stunting Dan Ibu Hamil Kek Di Desa Taman Kecamatan Taman Kab Pemalang - Abd Rosib; Muhammad Gafarurrozi; Anissa Selly; Oktaf Velani; Nur Rohmah Nuzulanita; Yessie Novitha; Indah Fitriyatus Salamah; Ibnu Yahya Dwinanda; Anggita Rahmawati; Aji Pangestu; Nazilatul Farida Agustina; Anggraini Dhuma Sukma Ningrum; Nuananda Dwi Handika (LPPI UMN AL WASHLIYAH, 2025)
Stunting is a significant chronic nutritional problem, especially in coastal areas such as Taman Village, Pemalang. This study aims to evaluate the effectiveness of the Supplementary Feeding (PMT) program in reducing the prevalence of stunting in toddlers and improving the nutritional status of pregnant women with Chronic Energy Deficiency (KEK) in Taman Village, Taman District, Pemalang Regency. Through a qualitative approach, this study identified factors that influence nutritional care practices in the community. Supplementary Feeding (PMT) of local food in the form of processed chicken rolade and carang gesing as one of the strategies to reduce stunting. This study indicates that the PMT program is an effective intervention in overcoming the problem of stunting in Taman Village.